Occupational Exposure to Benzene and Risk of Breast Cancer: Systematic Review and Meta-Analysis - Seyyedsalehi, Monireh Sadat; Destefano, Vincent; Shah, Darshi; Shah, Veer; Bonetti, Mattia; Boffetta, Paolo (La Medicina del Lavoro, 2024)
Introduction: Benzene is a recognized carcinogen; however, its association with breast cancer is not well established. Hence, a meta-analysis of cohort and case-control studies was performed to determine the association between occupational benzene exposure and the risk of breast cancer. Methods: A systematic literature review identified 7573 publications from which 23 cohort and case-control studies were retained and evaluated using meta-analyses (fixed effects model). PRISMA guidelines were followed. Our protocol was registered in the PROSPERO database (Registration No. CRD42022379720). Study quality was assessed using a modified Newcastle-Ottawa scale (NOS).Results: The summary relative risk (RR) for ever-benzene exposure was 1.08 (95% CI=1.03-1.14, I2=38.6%, n=23 risk estimates); corresponding RR for cancer incidence and mortality were 1.08 (95% CI=1.02-1.14, I2=56.1%, n=16) and 1.10 (95% CI=0.87-1.37, I2<0.001%, n=10). However, heterogeneity was detected for sex (p-het=0.002), publication year (p-het<0.001), study design (p-het<0.001), study quality (p-het<0.001), and industry of employment (p-het=0.03). The RR for high level of exposure showed positive association with breast cancer 1.35 (95% CI=1.06-1.72, I2 =<0.001%, n=3) and (P-het=0.64). Publication bias was detected (p=0.03).Conclusions: The results of our meta-analysis indicate a positive association between occupational benzene exposure and an increased risk of breast cancer, particularly when exposed to higher levels of benzene. However, bias and confounding could not be excluded.